Designing digital experiences for positive youth development from playpen to playground - Bers, Marina Umaschi (Oxford : Oxford University Press, 2012)
Based on over a decade and a half of research, this title aims to guide readers in the design of digital technologies to promote positive behaviours in children and teenagers.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Technology and children; Internet and children; Digital media; Youth development